2015
DOI: 10.1167/iovs.14-16053
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Detection of Choroidal Abnormalities Related to NF1: Feasibility and Comparison With Standard NIH Diagnostic Criteria in Pediatric Patients

Abstract: Neurofibromatosis type 1-related choroidal abnormalities represent a new diagnostic sign in NF1 children. The main advantage of this sign seems the theoretical possibility to anticipate NF1 diagnosis, whereas the main obstacle is the cooperation required by very young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
40
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 13 publications
(21 reference statements)
6
40
1
5
Order By: Relevance
“…Overall, the results and the conclusions of Parrozzani et al 1 are in accordance with our study. Therefore, they contribute to the evidence that the evaluation of choroidal abnormalities identified by NIR imaging should represent a new diagnostic sign in pediatric patients with NF1.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Overall, the results and the conclusions of Parrozzani et al 1 are in accordance with our study. Therefore, they contribute to the evidence that the evaluation of choroidal abnormalities identified by NIR imaging should represent a new diagnostic sign in pediatric patients with NF1.…”
supporting
confidence: 93%
“…We read with great interest the recent article by Parrozzani et al 1 regarding the choroidal abnormalities related to neurofibromatosis type 1 (NF1) in pediatric patients. The authors conducted a prospective, masked, cross-sectional study looking at feasibility and the diagnostic performance evaluation of NF1-related choroidal abnormalities.…”
mentioning
confidence: 99%
“…The largest pediatric study cohort was published by Parrozzani et al; 140 pediatric NF1 patients, 59 NF1 suspected patients and 42 healthy subjects were included. A sensitivity of 0.6 and a specificity of 0.97 were found . During the same period, Vagge et al reported nodules in 69.2% of 78 patients (age 8.1 years ± 3 years) .…”
Section: Discussionmentioning
confidence: 99%
“…All of our patients could participate in the study. Reported feasibility of this exam by Parrozani et al was 82%, for a pediatric age group 0–16 years old . With the upcoming enhanced eye tracking systems and advanced technology, data acquisition becomes fast (<2 s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation